FunRich: An open access standalone functional enrichment and interaction network analysis tool. Issue 15 (17th June 2015) - Pathan, Mohashin; Keerthikumar, Shivakumar; Ang, Ching‐Seng; Gangoda, Lahiru; Quek, Camelia Y.J.; Williamson, Nicholas A.; Mouradov, Dmitri; Sieber, Oliver M.; Simpson, Richard J.; Salim, Agus; Bacic, Antony; Hill, Andrew F.; et al.
<x xml:space="preserve">Abstract</x> As high‐throughput techniques including proteomics become more accessible to individual laboratories, there is an urgent need for a user‐friendly bioinformatics analysis system. Here, we describe FunRich, an open access, standalone functional enrichment and network analysis tool. FunRich is designed to be used by biologists with minimal or no support from computational and database experts. Using FunRich, users can perform functional enrichment analysis on background databases that are integrated from heterogeneous genomic and proteomic resources (>1.5 million annotations). Besides default human specific FunRich database, users can download data from the UniProt database, which currently supports 20 different taxonomies against which enrichment analysis can be performed. Moreover, the users can build their own custom databases and perform the enrichment analysis irrespective of organism. In addition to proteomics datasets, the custom database allows for the tool to be used for genomics, lipidomics and metabolomics datasets. Thus, FunRich allows for complete database customization and thereby permits for the tool to be exploited as a skeleton for enrichment analysis irrespective of the data type or organism used. FunRich (http://www.funrich.org) is user‐friendly and provides graphical representation (Venn, pie charts, bar graphs, column, heatmap and doughnuts) of the data with customizable font, scale and color (publication quality).